Finite element solution to engineering problems / G. Jagmohan Das - Das, G. Jagmohan (Universiti Teknologi MARA Kampus Samarahan, 1999)
This paper deals with the solution methodology to the engineering field problems with the application of Finite Element Method (FEM). Various types of boundary value problems that can be solved by FEM are indicated. Formulation of a mathematical model for a field problem and the steps of solution by FEM are explained. A case study of a heat conduction problem has been presented to demonstrate the implementation of an algorithm oriented computer program already developed. General conclusions on the application of FEM have been discussed.